Legal Regulatory Issues Regarding Parallel Import Activities in Indonesia - Gregorius Eka Januario CAB; Endang Prasetyawati (DiH: Jurnal Ilmu Hukum, 2026)
Parallel import is a legal phenomenon that often sparks debate in the context of trademark protection in Indonesia. This activity is frequently perceived as infringing the exclusive rights of trademark holders, although it simultaneously supports fair competition and provides broader access to imported goods. This study aims to analyze the legal regulatory issues surrounding parallel import activities and their implications for the legal protection of trademark holders. The research method used is normative legal research with statutory and conceptual approaches. Legal sources include primary legal materials, such as relevant laws, and secondary legal materials in the form of books, scholarly journals, and other supporting literature. The analysis is conducted descriptively to map the prevailing legal regulations and evaluate their effectiveness in providing legal protection. The study finds that the regulations regarding parallel imports in Indonesia still fail to provide adequate legal certainty. The absence of clear norms on the legality boundaries of parallel import activities creates uncertainty for both trademark holders and business actors. Additionally, inconsistencies in law enforcement exacerbate the situation. The findings recommend revising the regulations to not only reinforce legal protection for trademark holders but also consider the principles of fair competition. Such revisions are expected to create a balance between protecting the exclusive rights of trademark holders and meeting market demands for competitively priced imported goods.